Pengaruh Financial literacy Terhadap Preferensi Masyarakat Kabupaten Tanah Datar Memilih Produk-Produk Pendanaan Pada Perbankan Syariah - Febby Irfayunita; Hesi Eka Puteri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2019)
The purpose of this study investigates whether financial literacy affects the  preferences of choosing  the funding product at Islamic Banks. The research method used is a quantutative method that uses a sample of  385 customers of Islamic banks in Tanah Datar district, under condition 2018, this study reveals that financial literacy is positively associated with  the  preferences of choosing funding products.  This finding offer the empirical evidence of the importance on the relationship of financial literacy to the  preferences of choosing  the funding product. It indicates that the financial literacy  is a important point in Islamic banks thay will make peoples turn to Islamic banks . Furthermore, this research recommends strategy of increasing market share of Islamic Bank by increasing public’s finance literacy.